Implications of respiratory motion for small animal image-guided radiotherapy - Hill, M; Vojnovic, B (British Institute of Radiology, 2016)
Image-guided small animal irradiators have the potential to make a significant impact on facilitating the translation of radiobiological research into the clinic. To fully exploit the improved precision in dose delivery to the target/tumour while minimising dose to surrounding tissues, minimal positional error in the target is required. However, for many sites within the thorax and abdomen, respiratory motion may be a critical factor in limiting accuracy of beam delivery and until now, very little attention has been paid to the impact and management of this motion. We report on the implications of respiratory motion with respect to the negative impact of delivered dose distributions and their assessment, ways being developed to effectively manage this motion, so that beam delivery only occurs during the stationary resting phase of the breathing cycle, and comment on the need to effectively integrate these developments into the software used to plan and control beam delivery. Altogether, the implementation of respiratory gated imaging and beam delivery will lead to significant improvements in the precision in dose delivery and constitutes an important development for preclinical radiotherapy studies.